Sierra Leone : Public Expenditure Review for Water and Sanitation 2002 to 2009 - Bennett, Anthony (World Bank, Washington, DC, 2014)
This review focuses on how public expenditure translates into the delivery of water supply and sanitation services in rural and urban areas in Sierra Leone. It describes the legal and institutional framework for the allocation of resources assesses access to Water Supply and Sanitation (WSS) services and past sector performance, and analyzes public expenditure in the sector, including the factors affecting the efficiency of use of resources, and makes recommendations. Water supply includes the supply, distribution, and usage of water for drinking, food preparation, and hygiene. Sanitation is defined as the sanitary disposal of liquid waste and the promotion of hygienic practices. The review covers the period from 2002 to 2009, a period of reconstructing after a decade of upheavals. Since 2002, democracy and a stable environment for development have been re-established in the country, especially since the 2007 presidential elections. Sierra Leone remains one of the poorest countries in the world.